JENIS-JENIS PARASIT INTERNAL PADA FESES SAPI (Bos sp.) DI DESA LEMPUING KOTA BENGKULU - Kamilah, Santi Nurul; Wulandari, Dwi Ayu (Universitas Bengkulu, 2019)
Cows are one of the ruminant animals which have high economic value because they have various needs for human life. In Bengkulu many cattle farms are found, but this is not free from parasitic infections which have special disadvantages on very large cattle. The purpose of this study was to identification the types of parasites found in cow feces in the village of Lempuing Bengkulu. The research was conducted on 2 July-2 August 2018 at the UPTD Laboratory and Bengkulu Animal Health Clinic using three methods: the native method, the sedimentation method and the mammalian faecal sedimentation method with 3 faecal samples. In the nativemethod no parasites were found containing worm eggs. In the method of sedimentation of cow feces (Bos sp.) obtained positive results of parasites containing worm eggs of Ascaris sp., Schistosoma sp. and Oesophagostomum sp. In the mammalian faecal sedimentation method, the presence of parasitic worm eggs Fasciola sp. and Paramphistomum sp.